1990
DOI: 10.3382/ps.0690150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Energy Electron Irradiation of Chicken Meat on Salmonella and Aerobic Plate Count

Abstract: Four experiments were used to determine the effects of high-energy irradiation on the number of aerobic microorganisms and Salmonella on broiler breasts and thighs. Irradiation ranging from 100 to 700 kilorads (krads) was provided by a commercial-scale, electron-beam accelerator. Irradiation of broiler breast and thigh pieces with electron beams at levels of 100, 200, 300, 400, 500, and 600 krads showed that levels as low as 100 krads would eliminate Salmonella. When 33 thighs were tested after irradiation at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Most data on the antibacterial efficacy currently originate from studies examining meat products (Farkas, 1998). On chicken legs, irradiation of 1 kGy reduced aerobic bacteria by about 3.0 log CFU/g and increasing the dose yielded not further reductions (Heath, Owens, & Tesch, 1990). Another study irradiated poultry carcasses with 2-7 kGy (Nassar, Al-Mashhadi, Fawal, & Shalhat, 1997).…”
Section: Irradiationmentioning
confidence: 95%
“…Most data on the antibacterial efficacy currently originate from studies examining meat products (Farkas, 1998). On chicken legs, irradiation of 1 kGy reduced aerobic bacteria by about 3.0 log CFU/g and increasing the dose yielded not further reductions (Heath, Owens, & Tesch, 1990). Another study irradiated poultry carcasses with 2-7 kGy (Nassar, Al-Mashhadi, Fawal, & Shalhat, 1997).…”
Section: Irradiationmentioning
confidence: 95%
“…Heath et al (1990) reported that an electron beam irradiation of 1.0 kGy was effective in reducing Salmonella and aerobic bacteria in broiler thighs and breasts. Patterson (1995) reported a 5-log reduction of Campylobacter jejuni in sterile poultry mince after a 1.0 kGy electron beam treatment.…”
Section: Introductionmentioning
confidence: 99%
“…poultry products (7,16,27,28). The reports differ somewhat on the suggested optimal irradiation doses to simultaneously achieve safety in regard to Salmonella and to maximize organoleptic qualities of irradiated products.…”
mentioning
confidence: 99%